Long-Term Effects of Hypoxia-Reoxygenation on Thioredoxins in Rat Central Nervous System - Otero-losada, Matilde Estela (2020)
Oxidative stress induced by the oxidative pathway dysregulation following ischemia/reperfusion has been proposed as an important cause of neuronal death and brain damage. The proteins of the thioredoxin (Trx) family are crucial mediators of protein function regulating the intracellular hydrogen peroxide levels and redoxsensitive post-translational protein changes. This study evaluates the long-term effects of common carotid artery ligation-induced ischemia/reperfusion on the protein expression and distribution of fourteen members of the Trx family and related proteins (Grx1, Grx2, Grx3, Grx5, Prx1, Prx2, Prx3, Prx4, Prx5, Prx6, Trx1, Trx2, TrxR1, TrxR2) in the most hypoxia susceptible rat brain areas, namely, cerebellum, corpus striatum, and the hippocampus. The thioredoxin proteins displayed a complex, cell-type, and tissue-specific expression pattern following ischemia/reperfusion. Even 60 days after ischemia/reperfusion, Western blot analysis showed a persistent expression of Trx1 and Grx2 in several brain areas. Thioredoxins might participate in the long-term restoration of redox signaling, and the recovery of the affected tissues.